2020
DOI: 10.1037/neu0000592
|View full text |Cite
|
Sign up to set email alerts
|

Intact reversed language-dominance but exaggerated cognate effects in reading aloud of language switches in bilingual Alzheimer’s disease.

Abstract: Objective: The current study investigated how Alzheimer’s disease (AD) affects production of speech errors in reading-aloud of mixed-language passages with language switches on cognates (e.g., family/familia), noncognates (e.g., people/gente), and function words (the/la). Method: Twelve Spanish-English bilinguals with AD and 22 controls read-aloud 8 paragraphs in 4 conditions: (a) English-default content switches, (b) English-default function switches, (c) Spanish-default content switches, and (d) Spanish-defa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 98 publications
(184 reference statements)
1
16
0
Order By: Relevance
“…In addition, the hypothalamic-pituitary-adrenal (HPA) axis can affect the colonization and composition of intestinal flora by stimulating the secretion of adrenocortical hormones [ 12 ]. In turn, gut microbes and their metabolites can mediate neurophysiological processes including neurodevelopment, neurotransmission, immune activation of the central nervous system, and the integrity of the blood-brain barrier by regulating the maturation of microglia and astrocytes [ 13 ]. In the meanwhile, intestinal flora and their metabolites, such as short-chain fatty acids (SCFAs), γ -aminobutyric acid (GABA), and brain-derived neurotrophic factor (BDNF), have important effects on nerve inflammation, nerve injury, and brain behavior by regulating peripheral immune response [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hypothalamic-pituitary-adrenal (HPA) axis can affect the colonization and composition of intestinal flora by stimulating the secretion of adrenocortical hormones [ 12 ]. In turn, gut microbes and their metabolites can mediate neurophysiological processes including neurodevelopment, neurotransmission, immune activation of the central nervous system, and the integrity of the blood-brain barrier by regulating the maturation of microglia and astrocytes [ 13 ]. In the meanwhile, intestinal flora and their metabolites, such as short-chain fatty acids (SCFAs), γ -aminobutyric acid (GABA), and brain-derived neurotrophic factor (BDNF), have important effects on nerve inflammation, nerve injury, and brain behavior by regulating peripheral immune response [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it might be more meaningful to consider speakers who are highly proficient in their later-acquired language (i.e., reversed dominance bilinguals) for comparison. Although there is a growing body of research on their language use and processing (e.g., Declerck et al, 2020;Gollan et al, 2020), research examining the effects of their language input on their children's language development is scarce. In one recent study, Stoehr et al (2019) asked whether language development in Dutch-German bilingual pre-schoolers has been influenced by the language input from their sequential bilingual mothers, who acquired Dutch in their adulthood, and have been using it dominantly in their daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…However, if autocorrect errors also increase in association with an increased accumulation of amyloid or Tau in the brain, it might suggest that decline in monitoring and executive control processes needed to stop autocorrection are affected by healthy aging and magnified by unidentified preclinical AD. In previous studies of reading aloud in bilinguals with AD (Gollan et al, 2017(Gollan et al, , 2020, and healthy aging monolinguals reading paragraphs without malapropisms (Gollan & Goldrick, 2019), function words elicited more errors than content words, a result we attributed to the difficulty of monitoring function words (Staub, Dodge, & Cohen, 2019). Thus, we hypothesized that errors on function word targets (e.g., saying "with" instead of "within" in "She'd try to be careful but she'd always end up within food on her clothes") might be more sensitive to aging and/or AD-related CSF biomarker levels than content word errors (e.g., saying "evolve" instead of "involve" in "As this technology continues to involve and I continue to get older .…”
mentioning
confidence: 98%
“…Two recent studies demonstrated some promise along these lines using reading aloud of full paragraphs to elicit connected speech in cognitively healthy aging bilinguals versus in bilinguals with AD. Participants in these studies read aloud paragraphs written mostly in one language but with some switches into their other language; bilinguals with AD were more likely than controls to spontaneously translate language-switched words to avoid switching languages in their speech (Gollan, Li, Stasenko, & Salmon, 2020; Gollan, Stasenko, Li, & Salmon, 2017).…”
mentioning
confidence: 99%